Fundamentals of programming with examples in C, C++ and Java - Jamal Othman (Pusat Penerbitan Universiti (UPENA), 2011)
The purpose of this book is to give a basic overview of programming concepts using three different languages which are C, C++ and Java programming. This book enables readers and students to understand the steps in writing programs. The main target is to produce programs of the highest quality according to a certain standard.